FinTech, BigTech and Banks : digitalisation and its impact on banking business models - Tanda, Alessandra; Schena, Cristiana-Maria (SPRINGER NATURE, 2019)
This Palgrave Pivot analyses the evolution of strategies and business models adopted by financial operators that employ technological solutions to deliver financial products and services. The analysis is performed on a proprietary dataset built on different sources that highlight important differences in strategical approaches taken by FinTech companies, TechFin and BigTech, and banks (traditional and digital native). For each type, the authors underline their distinctive patterns, strengths and weaknesses. The main focus of the analysis in on the European market that is investigated also in the light of the difference and similarities with other markets (such as US and China). The unbundling and re-bundling of productive processes in finance, the treatment of information and the level of innovation in the customer relationship highlight the intense change that the banking activities of new financial services providers are currently dealing with, especially the retail segment. Despite the main international banks' implementation of innovative strategical approaches to take advantage of the digitalization of business and cope with competition, so far the level of the disruption brought by FinTech is not fully understood or widespread. This holds especially true for the smaller banks: the latter need to take a proactive approach to individuate a business model able to satisfy the new customer needs and the competitive pressure that are destined to increase and further evolve. This book addresses this and would appeal to academics, researchers and students of banking, FinTech and financial innovation alongside policy makers, regulatory authorities, FinTechs and banks.- Resumé vydavatel
Keywords: finanční služby; finanční analýza; bankovnictví; financial services industry; financial analysis; banking; elektronické knihy; kolektivní monografie; electronic books; collective monographs